Revalorization of Broccoli By-Products for Cosmetic Uses Using Supercritical Fluid Extraction - María Borja-Martínez; Jesús Lozano-Sánchez; Isabel Borrás-Linares; María A Pedreño; Ana B Sabater-Jara (MDPI AG, 2020)
The agri-food industry is currently one of the main engines of economic development worldwide. The region of Murcia is a reference area in Europe for the cultivation of fruits and vegetables and produces the bulk of Spanish exports of broccoli (Brassica oleracea var. italica). The processing of fresh produce generates a huge number of by-products that represent an important economic and environmental problem when discarded. In this work, an advanced extraction technique using environmentally friendly solvents was applied to assess the revalorization of broccoli by-products, by performing a comparative analysis with conventional extraction. To achieve this goal, supercritical fluid extraction based on response surface methodology was performed using CO2 and ethanol as solvents. The results obtained showed that the supercritical fluid extracts were rich in β-carotene, phenolic compounds, chlorophylls and phytosterols. Moreover, in bioactivity assays, the supercritical fluid extracts exhibited a high antioxidant activity and a cytoprotective effect in a non-tumorigenic keratinocyte cell line exposed to ultraviolet B light. The results indicate that supercritical fluid extracts from broccoli by-products could potentially serve as an ingredient for cosmetic purposes.